Effects of RANKL Knockdown by Virus-like Particle-Mediated RNAi in a Rat Model of Osteoporosis - Daniel B. Hoffmann; Jens Gruber; Kai O. Böker; Delia Deppe; Stephan Sehmisch; Arndt F. Schilling; Nicolas Lemus-Diaz; Marina Komrakova; Stefan Schneider (Elsevier, 2018)
Rebalancing of the RANKL/OPG system seems to be an effective treatment strategy in postmenopausal osteoporosis. Here, we evaluate the knockdown of RANKL by in-vivo-delivered siRNA in a rat model of osteoporosis. Virus-like-particles (VLPs) derived from polyoma JC virus were used for delivering RANKL siRNA in ovariectomized (OVX) rats. 48 rats were ovariectomized and treated with either 17β-estradiol (E2), VLPs containing RANKL siRNA (siRANKL), or VLPs containing non-cognate siRNA (siCtrl). All OVX groups were subdivided into the prophylaxis group (PG) and the therapy group (TG). The PG received treatment directly after being OVX for 10 weeks. The TG received treatment 5 weeks after being OVX for 5 weeks. Rats were sacrificed 10 weeks after being OVX. Bone and blood samples were analyzed. E2 and siRANKL showed a significant knockdown of RANKL mRNA. A protein knockdown was observed with E2 and siRANKL in the TG but not in the PG. No distinct improvements in biomechanical and morphological properties of the bones were observed after siRANKL treatment. In the PG, E2 protected the bone structure. We demonstrated successful mRNA and protein knockdown by VLP-mediated RNAi in vivo. Knockdown of membranous RANKL did not result in significant improvements of bone properties in this model of early-stage postmenopausal osteoporosis. Keywords: RANKL, osteoporosis, VLP, RNA interference